AUTOMATED ANALYSIS OF CELL DENSITY IN BREAST CANCER AS AN ADDITIONAL METHOD OF INCREASING OBJECTIVITY AND ACCURACY OF BREAST CANCER PROGNOSIS - R. M. Paltuev; A. G. Kudabergenova; V. F. Semiglazov; A. V. Komyakhov (ABV-press, 2017)
Introduction. In the last ten years, it became obvious that on the molecular level breast cancer is a group of heterogenous tumors. The current objective of routine clinical practice of treatment prescription includes accurate disease prognosis for every individual patient and conviction that the risk of breast cancer recurrence after adjuvant hormone therapy without adjuvant chemotherapy doesn't increase.The study objective is to evaluate how clinical use of risk associated with cell density can in practice improve prognosis of recurrence risk in patients with breast cancer after standard clinical and pathomorphological examinations.Materials and methods. The article analyzes therapy results using data from the cumulative cancer registry of breast cancer diagnosis and treatment of the N.N. Petrov National Medical Research Oncology Center in 2000-2009. The database includes information on diagnosis, treatment, and survival of 5106 patients with breast cancer. Archived material (from 2000 to 2009) from paraffin blocks of the "targeted group" for methods of molecular and genetic profiling was poured into recipient blocks, stained with corresponding antibodies such as widely used ER, PR, HER2/neu, Ki-67 markers as well as poorly studied markers: cell density, р53, CK5/6, CK14, CD4/CD8, p63, EGFR, FOXP3, AR, FOX1.Results. The study of 1118 patients with stage T1-2N0M0 breast cancer has shown that analysis of risk associated with cell density allows to predict disease outcome. Correlation between the marker and the grade of histological malignancy is more rare than for Ki-67 determined in this patient group. As a result, determination of cell density is an additional method to increase objectivity and accuracy of breast cancer prognosis.Conclusions. Automated cell density analysis for breast cancer is almost fully operator-independent which increases accuracy and objectivity of the results. Cell density in breast cancer lower than 3000 cells/mm2 is a favorable prognostic factor.